La comprensión lectora en niños de educación general básica elemental - Bravo, Jéssica O. (2023)
Comprehensive reading encompasses the understanding and interpretation of different types of texts based on prior knowledge, practice through constant reading, and the motivation that occurs when reading a book. This research was carried out because there is a need to improve the level of performance of reading skills.